Does fresh single embryo transfer outcome predict the result of a subsequent vitrified–warmed blastocyst of the same cohort?. (15th March 2022) - Hershko Klement, Anat; Tulandi, Togas; Hasson, Joseph; Tannus, Samer; Weitzner, Omer; Weon-Young, Son; Wiser, Amir; Shavit, Tal
Abstract: Reflecting the current trends, the utilization of frozen-thawed transfer cycles has been steadily increasing worldwide; outcome predictors of these cycles are therefore a major research goal. Our aim was to investigate whether the outcome of a fresh single blastocyst transfer (SBT) can serve as a prognostic factor for the subsequent vitrified–warmed SBT originating from the same cohort. A retrospective cohort study was performed at a single unit. Non-donor fresh cycles were analyzed as predictors of the following vitrified–warmed cycle. Only SBTs were included. Cycles designated to a freeze-all policy and cycles involving pre-implantation genetic analysis were excluded. A total of 1127 vitrified–warmed single blastocyst cycles were included. The indications for artificial reproductive technologies were comparable across the study groups. Vitrified–warmed cycles following a live birth outcome in the fresh cycle were more likely to result in a clinical pregnancy than those following a fresh cycle, which failed to reach a live birth. The same trend was observed for live birth rate following vitrified–warmed transfer in the fresh cycle. After correcting for possible confounders, age and embryo quality were significantly correlated with the chance for a live birth, but the previous fresh cycle did not affect the results. We therefore conclude that after adjustment for age, embryo quality and number of previous oocyte retrieval cycles, the fresh cycle outcome was not a significant influential factor for the following vitrified–warmed cycle.